Portas abertas, janelas fechadas: um estudo de caso sobre imigrantes e refugiados em uma escola p??blica - Santana, Alexsandro Junior de (2020)
This academic project, of bibliographic, documentary and field nature, has as research object the forms of reception for immigrant and refugee students. The research opted for the specific study of this school because it considers it expressive in receiving these students and for understanding the dynamics that are established there. The objective is to understand how the binomial hospitality / hostility with immigrants and refugees occurs in a public school in the city of S??o Paulo. Theoretical references were based on the dialogue and articulation of the ideas of Edgar Morin's complex thinking, highlighting the ethics of understanding, the reflection on the crisis of human values and the need to establish a solidary coexistence, as proposed by Zygmunt Bauman, and in combating xenophobia and defending coexistence as an important human right, according to Albuquerque J??nior. The migratory crisis caused the displacement of millions of people around the world, who were forced to leave their territories because of wars, armed conflicts, political and religious persecution, natural disasters, as well as for better living conditions. In the last decade, Brazil entered the international scene as a destination for the immigrant population. During this period, Haitians, Venezuelans, Congolese and Syrians were some of the asylum seekers in the country. The study revealed that education professionals, despite being at the forefront in welcoming children who are in a migratory flow, still feel unprepared to deal with the complexity of this phenomenon. Elements such as cultural and linguistic differences, public policies, teacher training and the students' own transience make it difficult for pedagogical work that can respond to this demand. However, it is possible to note that the school carries out actions that promote respect, dialogue and understanding between students, families, teachers and technical staff, in which differences do not separate, but enrich human relationships.